Insight into the conformational space of n-benzyl-n-(furan-2-ylmethyl) acetamide by NMR spectroscopy and DFT calculations - Corredor Montaña, Jeisson D. (2020)
In this study, the conformational behavior of N-benzyl-N-(furan-2-ylmethyl) acetamide in chloroform was addressed by using a combined experimental/theoretical strategy using NMR spectroscopy and quantum chemical calculations. The 1H and 13C one-dimensional NMR spectra, as well as the two-dimensional HSQC-DEPT and HMBC-DEPT NMR spectra, evinced the presence of a hindered cis(E)-trans(Z) rotational equilibrium in solution. DFT calculations were performed at different theoretical levels using the polarizable continuum model (PCM) and predicted nine (four Z and five E structures) stable conformations. The interconversion dynamics among the different confirmations were established in terms of four different rotational equilibria in CDCl3. The chemical shifts in the 1H and 13C NMR spectra of the compound are similar to the values calculated for the two most abundant conformational equilibria at room temperature, one caused by two Z rotamers and the other by two E rotamers. The compound was also characterized for the first time by FTIR, Raman spectroscopy, and GC/MS spectrometry. Additionally, several acylation methodologies for synthesizing the title compound from N-benzyl-1-(furan-2-yl)methanamine were tested which resulted in high yields (> 90%) under very convenient conditions (10 min, at room temperature).